Calbindin‐D28K Immunoreactivity in the Human Cerebellar Cortex. Issue 7 (10th April 2014) - Flace, Paolo; Lorusso, Loredana; Laiso, Giuliana; Rizzi, Anna; Cagiano, Raffaele; Nico, Beatrice; Ribatti, Domenico; Ambrosi, Glauco; Benagiano, Vincenzo
ABSTRACT Calbindin‐D28k (CB) is a calcium‐binding protein largely distributed in the cerebellum of various species of vertebrates. As regards the human cerebellar cortex, precise data on the distribution of CB have not yet been reported. Aim of the present work was to analyze the distribution of CB in postmortem samples of human cerebellar cortex using light microscopy immunohistochemical techniques. Immunoreactivity to CB was detected within neuronal bodies and processes distributed in all cortex layers. In the molecular layer, the immunoreactivity was observed in subpopulations of stellate and basket neurons. In the Purkinje neuron layer, the immunoreactivity was observed in practically all the Purkinje neurons. In the granular layer, the immunoreactivity was observed in subpopulations of granules, of Golgi neurons, and also of other types of large neurons (candelabrum, Lugaro neurons, etc.). Immunoreactivity to CB was also observed in axon terminals distributed throughout the cortex according to layer‐specific patterns of distribution. The qualitative and quantitative patterns of distribution of CB showed no difference among the different lobes of the cerebellar cortex. This study reports that CB is expressed by different neuron types, both inhibitory (GABAergic) and excitatory (glutamatergic), involved in both intrinsic and extrinsic circuits of the human cerebellar cortex. The study provides further insights on the functional role of CB and on the neuronal types of the cerebellar cortex in which it is expressed. Anat Rec, 297:1306–1315, 2014. © 2014 Wiley Periodicals, Inc.